Separation and Detection of Chlorpromazine Hydrochloride and Promethazine Hydrochloride Using Electrochemiluminescence Followed by Capillary Electrophoresis - LI, YUNHUI; WANG, CHUNYAN; TIAN, JIAN; LIU, XIAOQIU; YOU, TIANYAN (Asian Journal of Chemistry, 2010)
Phenothiazine drugs, chlorpromazine hydrochloride (CPZ) and promethazine hydrochloride (PMZ), were determined with Ru(bpy)32+ electrochemiluminescene by the capillary electrophoresis (CE-ECL). It was found that both CPZ and PMZ could produce an intermediate that acted as coreactants to react with Ru(bpy)32+ to produce excited states which were capable of emitting light. This CE-ECL detection method had high sensitivity, good selectivity and reproducibility for CPZ and PMZ determination. Under the optimized conditions: ECL detection at 1.15 V, 3.0 × 10-2 mol L-1 phosphate buffer at pH 4.0, 5.0 × 10-3 mol L-1 of Ru(bpy)32+ and 5.0 × 10-2 mol L-1 of phosphate buffer at pH 7.5 in the detection reservoir, the ECL intensity was linear with three orders for CPZ and two orders for PMZ and the detection limits (S/N = 3) were 1.0 × 10-8 mol L-1 for CPZ and 1.0 × 10-6 for PMZ mol L-1, respectively. The CE-ECL method was applied to analyze CPZ and PMZ in real samples including tablets and injections and satisfactory results were obtained without interference from samples matrix. The method was successfully applied to the determination of CPZ and PMZ in human urine.